Liposomes in dermatological diseases - Kamra, Manju; Diwan, A. (Journal of Applied Pharmaceutical Research, 2017)
Liposomes are vesicles comprising of spherical phospholipids making them useful for topical applications of drugs. Liposome research has been expanded considerably and nowadays, it is possible to construct a wide range of liposomes varying in size, phospholipids composition and surface characteristics. In dermatological diseases, the topical application of liposomes has proven to be of high therapeutic value. Liposomes can be used as carriers for hydrophilic as well as lipophilic therapeutic agents because of their amphipathic character. They may improve stabilization of instable drugs by encapsulating them. They have the potential to target drugs into the pilosebaceous structures and hence have an advantage for treatment of hair follicle-associated disorders. Liposomal encapsulated drugs are found useful in the treatment of acne, atopic dermatitis, psoriasis, vitiligo, superficial vein thrombosis and hair removal etc